The Efficacy of a Combination of Oral Antioxidants (Vitamin C, Vitamin E, and Alpha-Lipoic Acid) as an Adjuvant Therapy for Vitiligo: A Systematic Review and Narrative Synthesis - Irnayati Rahman; Antonius Wibowo; Putri Jati Utami (Green Publisher Indonesia, 2026)
Vitiligo is a chronic acquired depigmentation disorder characterized by progressive melanocyte destruction, affecting approximately 0.5–2% of the global population and causing significant psychosocial impairment. The involvement of oxidative stress in melanocyte damage has encouraged the exploration of antioxidant supplementation as an adjunctive therapeutic approach. This study aimed to evaluate the efficacy of oral antioxidant combinations, particularly vitamin C, vitamin E, and alpha-lipoic acid (ALA), as adjunctive therapies for vitiligo and to assess the consistency of available clinical evidence. A systematic review and narrative synthesis were conducted following the PRISMA 2020 guidelines. Literature searches were performed in PubMed/MEDLINE, the Cochrane Library, Scopus, ScienceDirect, Google Scholar, and ClinicalTrials.gov. Eligible studies included randomized controlled trials evaluating oral antioxidant combinations combined with conventional vitiligo therapies, with outcomes including repigmentation, oxidative stress biomarkers, quality of life, and adverse effects. Two randomized controlled trials involving patients with vitiligo met the inclusion criteria. The findings demonstrated that antioxidant combinations, particularly ALA, vitamin C, and vitamin E combined with narrowband ultraviolet B (NB-UVB) therapy, showed potential benefits in improving repigmentation and reducing oxidative stress markers. However, another study reported no significant additional clinical improvement, indicating inconsistent outcomes influenced by disease subtype, lesion extent, treatment duration, and therapeutic protocols. In conclusion, oral antioxidant combinations represent a promising complementary therapy for vitiligo; however, current evidence remains insufficient to support their routine clinical application. Further large-scale randomized clinical trials with standardized protocols are required to establish their effectiveness and clinical relevance.